DETERMINANTS ANALYSIS OF NET INTEREST MARGIN USING BANK-SPECIFIC VARIABLES AND MACROECONOMIC FACTORS OF COMMERCIAL BANKS IN INDONESIA - Dwiansyah (19015111), Fachri
Banks have a major role that affects the economic growth of a country. Banking serves as the main source of financing in order to drive the economic growth. Given the important role of bank in a country economy, the performance of commercial banks gets a great deal of attention in the economic literature. According to Bank Indonesia, the total asset of commercial banks in the period of 2008-2017 is increasing. Contrarily, the trend of NIM is decreasing. Thus this phenomenon indicates a possible decrease in commercial banks efficiency. This study aims to identify the relationship between bank-specific variables: Bank Size (LNSIZE), Capital Adequacy Ratio (CAR), Credit to Total Asset Ratio (CRDTA), Operating Cost to Operating Income Ratio (BOPO), Non-Performing Loans (NPL) and macroeconomic factors : Inflation Rate (INFL), and Gross Domestic Products Growth (GDP) toward Net Interest Margin (NIM) in 19 commercial banks in Indonesia, which included in BUKU 3 and 4 in the period of 2008-2017. The data used in this research is published financial statements and macroeconomic data from Otoritas Jasa Keuangan and Bank Indonesia. The data is analyzed using panel data regression with random effect method. The findings of this research indicated that the independent variables that Capital Adequacy Ratio, Credit to Total Asset Ratio, Non-Performing Loan and Inflation Rate appeared to have positive significant relationship to Net Interest Margin, while Bank Size and Operating Expense to Operating Income indicated to have a negative significant effect in the significance level of 0.05. From the intercept analysis, each banks appeared to have various differences on their NIM in the research period, with a gap of 12.7412% between the highest and least increase. Commercial banks should pay more attention to the significant variables in order to maintain their NIM. Operational coverage, variability of products, and brand recognition are also essential to increase their market share, which can lead to be a more efficient, healthy, and attractive bank.